(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
The research was caried out at Al Ghab Scientific Agriculture Research Center, during seasons 2019/2020 to study the effect of four rates of organic fertilizer 0 , 10 , 20 and 30 ton/ h, and five nitrogen fertilizer rates 0, 40, 80, 120 and 160 kg/h and the interaction between these rates on growth and seed yield of black cumin plant. The treatments were arranged in a split plot in a randomized complete block design (RCBD) with three replications. The organic fertilizer rates were assigned to the main plots and nitrogen rates were factorialy assigned to the sub plots. The results indicate the following. - The organic rate 30 ton/h significantly increased root length 16.61 cm, plant height 54.42 cm, total number of branches (29.16) and seed yield/plant 8.34 g compared to the control and the rate 10 ton/ha, while the rate 20 ton/ha gave higher capsule number 39.33, but there was no significant increase between the rate 20 and 30 ton/h, at all studied indicators. All nitrogen fertilizer rates caused an increase in all the indicators mentioned above, the rate 120 kg/h gave higher value in root length 16.42 cm, plant height 56.60 cm, branches number 28.15, capsule number 40.45, and seed yield/plant 8.91 g. On other hand, the rate 160 kg/h a decreased all indicators values. The interaction between organic rate 20 ton/h and the nitrogen rate 120 kg/h gave beter values for root length 18.49 cm, total brunches number 32.22, capsule number 47.67 and seed yield per plant 9.56 g. There was a higher plant height 60.20 cm at the interaction between (organic rate 30 ton/h × 160 kg N/h).